Nghiên cứu chế tạo điện cực PbO2/Ti và tính chất điện hóa của chúng trong môi trường chất điện ly - Sén, Trịnh Xuân; Hạnh, Trương Thị; Bích Lộc, Nguyễn Thị; Tùy, Trần Quốc (Vietnam Journal of Chemistry, 2014)
Using electrolytic method of the mixed solution of salts Pb(NO3)2, Al(NO3)3and Cu(NO3)2,electrodes of PbO2/Ti were made. By measuring the anodic polarization curves of these electrodes in Na2SO4solutions showed that the stability of the anodic polarization of PbO2/Ti electrode increased by the presence of α-PbO2thin films. The thickness of β-PbO2on the α-PbO2/Ti subtrate effects on the durability and electronic exchange ability of PbO2/Ti. On the other hands, the durability of the coating film β-PbO2, α-PbO2, SnO2/Ti in NaCl, Na2SO4and Na3PO4solutions is higher than others.